2005
DOI: 10.1111/j.1365-2214.2005.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit of local performance compared with standards recommended by the national guidelines for aetiologic investigation of permanent childhood hearing impairment

Abstract: Our study identified key areas where guidelines were not followed. These were related to lack of funding and parental choice. This sample has a higher connexin 'hit' rate for lesser degree deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Radiologic examination in small children often needs some form of anesthesia, which should be used to concurrently plan additional evaluations. However, the local setting might prevent any endeavour to optimize the organization of assessments [4,7].…”
Section: Resultsmentioning
confidence: 99%
“…Radiologic examination in small children often needs some form of anesthesia, which should be used to concurrently plan additional evaluations. However, the local setting might prevent any endeavour to optimize the organization of assessments [4,7].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies (31) employed computed tomography (CT) with, where indicated, 1 to 2 mm slice thickness. Magnetic resonance imaging (MRI) was additionally performed in 16 studies [24,26,32,33,37,45,50,53,54,[58][59][60][101][102][103] (table 3). Kimani et al reported MRI results only [47].…”
Section: Literature Analysis: Investigationsmentioning
confidence: 99%
“…This is especially true for genetic analysis, which is expensive. An audit in the UK found that guidelines for an aetiological investigation were only partially followed [60]. As in Switzerland, lack of funding and parental choice were key reasons why the guidelines were not followed.…”
Section: Analysis Of the Current Swiss Approach And Costsmentioning
confidence: 99%
“…3, 4 Jervell-Lange-Nielsen syndrome is a recessively inherited association between long QT interval and congenital deafness, and is characterised by a risk of syncope and sudden death due to a variety of polymorphic ventricular tachycardia. 7,8 The current study aimed (1) to survey UK practice regarding ECG screening of deaf children referred to cochlear implant centres, and (2) to review our local practice. This is thought to be an underestimate, because of the failure to make a diagnosis before sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of aetiological investigation of children with severe hearing loss have indicated a low compliance with ECG evaluation, despite recommendations 7 , 8 . The current study aimed (1) to survey UK practice regarding ECG screening of deaf children referred to cochlear implant centres, and (2) to review our local practice.…”
Section: Introductionmentioning
confidence: 99%